Bosutinib therapy resulting in severe deterioration of pre-existing pulmonary arterial hypertension. Issue 5 (22nd September 2016) - Hickey, Peter M.; Thompson, Alfred A.R.; Charalampopoulos, Athanasios; Elliot, Charles A.; Hamilton, Neil; Kiely, David G.; Lawrie, Allan; Sabroe, Ian; Condliffe, Robin
We read with interest the recent correspondence from Quilot et al. [1] describing a likely case of ponatinib-associated pulmonary arterial hypertension (PAH). The authors hypothesised that the mechanism by which tyrosine kinase inhibitors (TKIs) such as dasatinib and ponatinib, used for the treatment of chronic myeloid leukaemia (CML), induce PAH may involve their common inhibition of the non-receptor tyrosine kinase, Src [1]. Here, we present a patient who developed marked worsening of pre-existing TKI-associated PAH following commencement of bosutinib, a third-generation TKI also known to inhibit Src [2]. After marked improvement on withdrawal of bosutinib, the patient experienced further significant worsening of PAH after commencing ponatinib. We believe this is the first reported case linking bosutinib with PAH. It also supports the association between ponatinib and PAH and represents the first time that the development or worsening of PAH associated with multiple TKIs in the same patient has been reported. A patient with severe worsening of pre-existing PAH following treatment with bosutinib improved on cessation http://ow.ly/gJy7302uXL7